Nanoemulsions for health, food, and cosmetics: a review - Ashaolu, Tolulope Joshua (Environ Chem Lett, 2021)
Nanoemulsions are gaining importance in healthcare and cosmetics sectors as a result of the unique properties of nanosized droplets, such as high surface area. Here we review nanotechnology and nanoemulsions with focus on emulsifiers and nanoemulsifiers, and applications for drugs and vaccines delivery, cancer therapy, inflammation treatment, cosmetics, perfumes, polymers, and food. We discuss nanoemulsion safety and properties, e.g., stability, emulsification, solubility, molecular number and arrangements, ionic strength, pH and temperature.